Justice and utility: Approval of gender quotas to increase gender balance in top‐level managements—lessons from Iceland - Axelsdóttir, Laufey; Einarsdóttir, Þorgerður J.; Rafnsdóttir, Guðbjörg Linda (Gender, Work & Organization, 2023)
Abstract Despite the adoption of board gender quotas in several countries, little is known about the views on quotas outside the boards. In this article, we expand the dialogue about gender quotas by examining managers' arguments (justice and utility) for quotas as a measure to increase gender balance in top‐level managements. Drawing on a survey of 504 men and women managers in 244 of Iceland's largest companies, we show that social‐justice arguments and utility arguments make a stronger case for gender quotas than individual‐justice arguments. By highlighting the gendered context of arguments and expectations for further influence of gender quotas, we show that men managers' emphasis on liberal individualism and the lack of approval of quotas may hinder more organizational gender equality. We argue for the need to focus on organizational factors and top managers' responsibilities to support further gender balance in top‐level managements.